Geopolitics and the green revolution : wheat, genes, and the cold war - Perkins, John H. (Oxford University Press, 1997)
Perkins explores why four countries each sought to develop high yielding wheat production. National security concerns and management of foreign exchange were prime motivators of the new technologies, a relationship that has not been previously developed in studies of agricultural modernization.